Anesthesia techniques and the risk of complications as reflected in the European Registry of Quality Outcomes for Cataract and Refractive Surgery. Issue 12 (8th December 2022) - Segers, Maartje H.M.; Rosen, Paul; van den Biggelaar, Frank J.H.M.; Brocato, Lucia; Henry, Ype P.; Nuijts, Rudy M.M.A.; Tassignon, Marie-José; Young, David; Stenevi, Ulf; Behndig, Anders; Lundström, Mats; Dickman, Mor M.
Abstract : The use of topical anesthesia for cataract surgery increased over time. Topical anesthesia is associated with an increased risk of posterior capsule rupture, with and without dropped nucleus, and endophthalmitis. Abstract : Purpose: To determine the trends in anesthesia techniques for cataract surgery over the past decade and their relationship to surgical complications. Setting: Clinics affiliated with the European Registry of Quality Outcomes for Cataract and Refractive Surgery (EUREQUO). Design: Retrospective cross-sectional register-based study. Methods: Variables include patient demographics, visual acuity, ocular comorbidities, surgery characteristics, intraoperative complications, and postoperative complications for the study period from January 2008, to December 2018. The anesthesia methods registered in the EUREQUO and included in the study are topical, combined topical and intracameral, sub-Tenon, regional, and general anesthesia. Multivariate logistic regression models for each complication were constructed to estimate the adjusted odds ratio (OR) and 95% CIs. Results: Complete data were available of 1 354 036 cataract surgeries. Topical anesthesia increased significantly over time (from 30% to 76%, P < .001). Sub-Tenon and regional anesthesia decreased (from 27% and 38% to 16% and 6%, respectively, P < .001), and general and combined topical and intracameral anesthesia remained stable (around 2%). Sub-Tenon (OR, 0.80; 95% CI, 0.71-0.91, P < .001), regional (0.74; 95% CI, 0.71-0.78, P < .001), general (0.53; 95% CI, 0.50-0.56, P < .001), and intracameral anesthesia (0.76; 95% CI, 0.64-0.90, P = .001) carried a significantly decreased risk of posterior capsule rupture (PCR), with and without dropped nucleus, compared with topical anesthesia. The risk of endophthalmitis was significantly lower with regional anesthesia compared with topical anesthesia (OR, 0.60; 95% CI, 0.44-0.82, P = .001). Conclusions: The use of topical anesthesia for cataract surgery increased over time. Topical anesthesia is associated with an increased risk of PCR with and without dropped nucleus, and endophthalmitis.